Synthesis and characterization of Cu-based telluride semiconductor materials for application in photovoltaic cells - Ntholeng, Nthabiseng (My University, 2017)
The colloidal method has extensively been used to synthesize ternary and quaternary copper sulfides and selenides. Although tellurides form part of the chalcogenides, little has been reported on them particularly the synthesis of these nanostructures. Achieving high-quality nanocrystals through colloidal synthesis requires thorough monitoring of parameters such as time, solvent, precursor as they affect nucleation and growth of the nanocrystals. Herein, we report on the colloidal synthesis of ternary CuInTe2 and quaternary CuIn1-xGaxTe2 nanostructured semiconductor materials. A typical synthesis of CuInTe2 entailed varying reaction temperature. At temperatures below 250 °C, no formation of CuInTe2 was seen. At 250 °C formation of CuInTe2 could be observed with the formation of binary impurities. A change in the sequence in which precursors were added at 250 °C yielded pure CuInTe2. Applying different surfactants aided in achieving differently structured morphologies of CuInTe2 nanocrystals. Morphology varied from rods, cubes, nanosheets etc. Different morphologies resulted in different optical properties with the high optical band gap of 1.22 eV measured for 1D rods. Different precursors were employed in the synthesis of quaternary CuIn1-xGaxTe2. Precursor 2 (entailed the use of Cu (acac)2, In (acac)3 and Ga(acac)3) yielded pure CuIn1-xGaxTe2 phase with no formation of impurities. Variation in reaction time influenced the optical properties of the quaternary CuIn1-xGaxTe2 with high band gap obtained at low reaction time (30 min). A change in Ga and In concentration resulted in reduced lattice parameters a and c with lowest values obtained with the highest Ga concentration. However, achieving the intended concentration proved challenging due to the loss of the material during synthesis. Increasing the Ga concentration resulted in a high optical band gap. Conducting the reaction with Hexadecylamine (HDA) resulted in a relatively high optical band though the formation of impurities was evident. The obtained band gap can be attributed to small sized particles as evident from TEM results. Heterojunction ZnO/CIT and ZnO/CIGT solar cell devices were fabricated through a simple solution approach. The performance of ZnO/CIGT device was superior to that of ZnO/CIT in which efficiency increased from 0.26-0.78%. In the ZnO/CIT device, high Voc of 880 mV was recorded while 573.66 mV was measured for ZnO/CIGT device. Chemical and thermal treatments were performed on the ZnO/CIGT devices. The efficiency increased from 0.78 1.25% when the device was chemically treated with a short-chain EDT ligand. A high conversion efficiency of 2.14% was recorded for devices annealed at 300 °C. High annealing temperatures resulted in poor device performance with the lowest efficiency of 0.089% obtained at annealing temperatures of 500 °C attributed to the leaching out of In and Ga into the ZnO layer.
Submitted to the Faculty of Science, School of Chemistry at University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 05 June 2017.
Keywords: Photovoltaic cells; Copper; Semiconductor nanocrystals